1992
DOI: 10.1128/iai.60.6.2547-2550.1992
|View full text |Cite
|
Sign up to set email alerts
|

Early complement components enhance neutralization of Chlamydia trachomatis infectivity by human sera

Abstract: Immunoglobulin G in human serum neutralizes chlamydial infectivity in vitro. Complement-intact, C5-depleted, and C8-depleted human serum all have significantly more neutralizing activity than serum heated to inactivate early components of complement. Cobra venom factor, an analog of human C3b, enhances neutralization of antichlamydial immunoglobulin G in the absence of early complement components. Chiamydia trachomatis infects mucous membranes of human eyes and genital tracts and causes chronic inflammation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These results are consistent with previous studies demonstrating that the alternative pathway-mediated neutralization of different C. trachomatis serovars is more efficient than that by the classical pathway, especially at higher serum concentrations (13).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous studies demonstrating that the alternative pathway-mediated neutralization of different C. trachomatis serovars is more efficient than that by the classical pathway, especially at higher serum concentrations (13).…”
Section: Discussionsupporting
confidence: 93%
“…For example, antibody neutralization of serovar K by heat-inactivated human serum in phagocyte-free medium is augmented only if cobra venom factor, a surrogate for C3, is added. This effect appears to be serovar dependent, as it did not occur with the L2 serovar (14).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These data raise the possibility that C5b-C8 recruitment of C9 and pore formation may lead to fatal disruption of the chlamydial envelope; yet, formation of the MAC appears to be dispensable as a primary control mechanism for Chlamydia infections. Depletion of factors C5 and C8 from serum had no effect on in vitro anti-chlamydial activity (24). Additionally, C. muridarum shedding and ascension into the upper genital tract was not impacted in C5-deficient mice (29).…”
Section: The C9 Macpf Domainmentioning
confidence: 93%
“…Complement activation clearly occurs during chlamydial infection with the antibody-independent alternative pathway playing a major role (21). Multiple studies using a tissueculture infection model have demonstrated that Chlamydia inclusion formation is significantly inhibited when EBs are pre-incubated with normal human sera (21)(22)(23)(24)(25) indicating complement factors may be important for controlling infection.…”
Section: The C9 Macpf Domainmentioning
confidence: 99%